PERKEMBANGAN POLITIK DAN KEBIJAKAN PENDIDIKAN ISLAM DI INDONESIA - Sumarto . (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2017)
Policy analysis is closely related to the political system with the content of communication and the use of knowledge relevant to the policy is central to the practice and theory of policy analysis. Only when knowledge of the kebiajakn-making process is communicated within the process can policy actors use such knowledge to improve public policy.The methodology of policy analysis is the standard system, the rules and procedures for creating, critically appraising, and communicating knowledge relevant to the policy. The methodology of policy analysis has several key characteristics: high attention to the formulation and problem solving, commitment to a descriptive and value-critical assessment and the desire to improve the efficiency of choice among a number of policy alternatives.This paper describes the nature and history of public Islamic education policy where the Ministry of Religious Affairs RI as the policy holder and UIN Syarif Hidayatullah Jakarta as implementer or implicated from the policy. Starting from the preparation of the agenda, policy formulation, policy adoption, policy implementation and policy assessment. Based on interviews and documentation conducted by the author. Especially want to answer the question of why every ministry has an educational institution, whereas there is already a national education ministry that regulates education in Indonesia, so there is a presumption that the existence of distrust with the ministry of national education as education providers